THE ADDITIONAL PULSATION POWER LOSS IN POWER CHAINS OF XPS DC - Sablin, O. I. (Science and Transport Progress, 2007)
Results of researches are stated in article specifying on consumption of inactive jet capacity by the electric rolling stock of a direct current. It is shown, that this consumption brings to additional loss of electric power.